Factors influencing electronic word of mouth (eWOM) intention among homestay customers : information system context - Nur Faeza Mohd Mairat (2016)
This study is to identify the factors influencing Homestay customers towards eWOM intention in Information System (IS) field. As an affordable alternative accommodation that serves unique environment, Homestay deliverables are still very difficult to be evaluated among consumers. Across the continuous demand for Homestay services, overwhelming online information causing consumers to depend on eWOM as it is easier to refine and reflect the actual quality of services. In fact, the acceleration of mobile sharing concept has permitted a splendid fast of eWOM dissemination thus influence the decision making of travelers. Therefore it is important that this study identifies the factors influencing eWOM intention in IS field to help Homestay managers dominates their market with minimal resources rather than costly and poorer results of traditional advertising. Thus this study aims to close the research gap by adopting Theory of Information System Success by Delone and Mclean (2003). In order to ensure a refined data was attained, set of questionnaires were administered to 300 random sampling populations who had experienced with Homestay website and services within the past six months. The data was analyzed using SmartPLS Version 2 M3. The results of Structural Equation Modelling (SEM) analysis shows that the a few factors influencing eWOM and it had been discovered that satisfaction mediates relationships between perceived quality and eWOM intention.